1975
DOI: 10.1152/ajplegacy.1975.228.1.80
|View full text |Cite
|
Sign up to set email alerts
|

Control of hepatic glycogen metabolism in the rhesus monkey: effect of glucose, insulin, and glucagon administration

Abstract: The effects of intravenous glucose, insulin and glucagon admininistration on the hepatic glycogen synthase and glycogen phosphorylase systems were assessed in the anesthetized rhesus monkey. Results were correlated with measurements of hepatic cyclic AMP (cAMP) concentrations and plasma glucose, insulin, and glucagon concentrations. Both glucose and insulin administration promoted significant inactivation of phosphorylase by 1 min, which was followed by more gradual activation of synthase. Neither glucose nor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
8
0
1

Year Published

1975
1975
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(12 citation statements)
references
References 0 publications
3
8
0
1
Order By: Relevance
“…In man, Liljenquist and co-workers (1) observed that the sustained infusion of exogenous glucagon at a constant rate is accompanied by a peak-decline pattern in net splanchnic cAMP production. Our own previous studies (2) and those of others (3,4) have noted a similar tendency for the hepatic cAMP content of experimental animals to decline from early peak levels during glucagon infusions. Further, in rats with persistent endogenous hyperglucagonemia induced by infection, the hepatic cAMP response to exogenous glucagon is blunted (5).…”
supporting
confidence: 82%
“…In man, Liljenquist and co-workers (1) observed that the sustained infusion of exogenous glucagon at a constant rate is accompanied by a peak-decline pattern in net splanchnic cAMP production. Our own previous studies (2) and those of others (3,4) have noted a similar tendency for the hepatic cAMP content of experimental animals to decline from early peak levels during glucagon infusions. Further, in rats with persistent endogenous hyperglucagonemia induced by infection, the hepatic cAMP response to exogenous glucagon is blunted (5).…”
supporting
confidence: 82%
“…The present findings in primate fetal liver are analogous to those previously observed with isolated fetal rat liver explants in culture (9). We therefore speculate that direct (glucose concentration-dependent) regulation of glycogen synthetase activity and glycogen synthesis, present in adult mammalian liver (5,7,16,(18)(19)(20), is not developed during early neonatal life. This may contribute to the low plasma glucose removal rates after bolus glucose injection observed at this time (2,4,15,20,30).…”
Section: Discussionsupporting
confidence: 89%
“…an appropriate reduction of endogenous glucose production and Six blood Sam les were obtained during the turnover period for B will achieve a new steady state concentration of plasma glucose glucose 3~ and ' C specific activity. Deproteinized plasma samples by insulin which inhibits gluconeogenesis and glycogenolysis and were passed through Dowex-1 (Cl-) and Dowex-50 (H') resin stimulates glycogenesis (4,6,17). In adults, after hepatic glycogen columns to separate glucose from lactate and charged glucose stores are depleted, gluconeogenesis is the most important regu-metabolites (5).…”
Section: Discussionmentioning
confidence: 99%
“…Insulin inhibits glycogenolysis and gluconeogenesis and enhances glycogenesis resulting in the net suppression of endogenous glucose production (4,6,17). Our data show that a moderate elevation of plasma insulin level effectively reduced gluconeogenesis (groups 2 and 4), but did not influence endogenous glucose production.…”
Section: Discussionmentioning
confidence: 99%